DETERMINAN STRUKTUR KEPEMILIKAN DAN FINANCIAL DISTRESS TERHADAP KONSERVATISME AKUNTANSI - Budi Santoso (Jurnal Ilmiah Akuntansi Indonesia, 2018)
The purpose of this study was to examine the effect of managerial ownership structure and financial distress to accounting conservatism. The population in this study is a manufacturing company that is listed on the Indonesia Stock Exchange (IDX) the period of 2016 to 2017 with a sample of 60 companies. Sampling technique in this study using purposive sampling technique.Processing and  data  analysis  using  SPSS.  The  test  data  used  is  multiple  linear regression analysis, the classical assumption test, and test hypotheses. The results of this study indicate that managerial ownership structure has no effect on accounting conservatism, while financial distress significantly influence accounting conservatism.Keywords: Accounting Conservatism, Financial Distress, Managerial Ownership Structure